2017
DOI: 10.1128/jcm.00550-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus in Self-Taken Samples from Screening Nonattenders

Abstract: The Copenhagen Self-Sampling Initiative (CSi) has shown how human papillomavirus (HPV)-based self-sampling can be used to increase screening participation among 23,632 nonattenders in the Capital Region of Denmark. In this study, we describe HPV prevalence and genotype frequency in 4,824 self-samples as determined by three HPV assays (the CLART, Onclarity, and Hybrid Capture 2 [HC2] assays) and compare the results with those for physician-taken follow-up samples. The HPV self-sample findings were also compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
14
3
Order By: Relevance
“…The higher DNA copy amount in vaginal self‐samples is consistent with the results of our previous study using the same device and HPV analysis . Recently, Lam et al also showed a higher amount of human DNA when performing self‐sampling as compared to samples collected by physicians from the same women …”
Section: Discussionsupporting
confidence: 90%
“…The higher DNA copy amount in vaginal self‐samples is consistent with the results of our previous study using the same device and HPV analysis . Recently, Lam et al also showed a higher amount of human DNA when performing self‐sampling as compared to samples collected by physicians from the same women …”
Section: Discussionsupporting
confidence: 90%
“…Both studies transferred the swab directly into the cobas PCR media at the point of collection, and as such there are currently no data on the stability of a swab transported dry to a laboratory before being resuspended into this media. BD diluent has been used as buffer, but only in an ad hoc method rather than using the commercially available diluent tubes [57].…”
Section: Pre-analytic Considerationsmentioning
confidence: 99%
“…The Roche cobas 4800 HPV test (Roche Molecular Systems, Pleasanton, CA) (12,13) provides HPV16 and HPV18 genotyping and reports 12 other high-risk HPVs (types 31,33,35,39,45,51,52,56,58,59, 66, and 68) as a pooled result (12) (The inclusion of HPV66 in cervical screening tests is based on a now corrected International Agency for Research on Cancer (IARC) evaluation, but HPV66 was incorporated into HPV testing, and given the difficulty in changing test formats, it remains.) Onclarity identifies six genotypes individually (types 16,18,31,45, 51, and 52), and the remaining eight HPV genotypes are reported in three channels (types 33/58, 56/59/66, and 35/39/68); this test has recently been FDA approved for clinical use to identify types 16, 18, and 45. cobas and Onclarity are the only two tests approved by the FDA for primary HPV screening (without the need for a cytologic component for cotesting).…”
mentioning
confidence: 99%
“…Previously reported performance data based on research studies and clinical use in Europe suggest that Onclarity might become a useful HPV test in the United States in the years ahead (6,(14)(15)(16)(17)(18)(19)(20)(21)(22). This analysis aimed to validate BD Onclarity further by assessing (i) the association of Onclarity types/channels with precancer/cancer (classified as cervical intraepithelial neoplasia grade 3ϩ [CIN3ϩ], with secondary consideration of CIN2), (ii) hierarchical and nonhierarchical HPV type/channel agreement (HPV16, HPV18, and 12 other high-risk types) between Onclarity and cobas results, and (iii) Onclarity typing for all types/channels compared to a linear array (LA).…”
mentioning
confidence: 99%